The correlation of Diet With Diabetes Millitus Patient’s Glucose Levels In Poli Dalam RSUD Dr. R. Koesma Tuban Distric - lilia faridatul fauziah (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
ABSTRACT Chronic disease is a condition or health problem that is associated with symptoms or disability requiring long-term management. DIABETES MILLITUS is a chronic disease, thus requiring appropriate treatment in order to control glucose levels in a normal or stable state and prevent complications. The purpose of this study was to determine the correlation of diet to with Diabetes Millitus patient’s glucose levels.This study uses Analytic Observational study designs with correlational design involved 48 respondents taken by simple random sampling. The collection of data by observation and interviews. Data were analyzed using Phi coefficient test with level of significance p˂α (0.05).Based on the results, 27 (56.25%) of the respondents had uncontrolled glucose levels. The results of the analysis show the Phi coefficient test p = 0.017, which means there is H0 is rejected, so that there is correlation diet to with Diabetes Millitus patient’s glucose levels.From the description above it can be concluded that adjusting the diet can to control glucose levels. It can be used as a healthy program to realize helathy people have the independence toward other people or drugs.